Social networks and Indian farmers’ demand for agricultural custom hire services - Magnan, Nicholas; Spielman, David J.; Lybbert, Travis J.; Gulati, Kajal; International Maize and Wheat Improvement Center; International Food Policy Research Institute; International Livestock Research Institute; International Rice Research Institute; WorldFish (International Food Policy Research Institute, 2014)
It is difficult to tell who influences farmers’ adoption decisions, and whether farmers use the same technologies as others in their network because they learn from or mimic each other or because they share similar characteristics and circumstances. This study1 used a set of experimental auctions coupled with randomly deciding which winners of the auctions actually received the technology to assess whether having first-generation adopters of a new resource-conserving technology – in this case, laser land leveling (LLL) – in a farmer’s network increases his or her exposure to and demand for the technology.